2017
DOI: 10.1080/13504622.2017.1307944
|View full text |Cite
|
Sign up to set email alerts
|

Teaching sustainability in Norway, China and Ghana: challenges to the UN programme

Abstract: The article compares how the UN-initiated education for sustainable development (ESD) has fared in three seemingly dissimilar countries: Norway, a wealthy, 'post-materialist' liberal democracy, Ghana, a developing democratic country, and China, a fast catching-up, centrallysteered economy. The studybased on an analysis of national ESD programmes, schoolbooks and qualitative interviews with teachers and studentsdiscusses some of the pivotal reasons for the decline in ESD schooling in all three countries. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
3
28
0
1
Order By: Relevance
“…In spite of being a significant contributor to climate change, China has taken a stance of leading through action rather than forcing other nations in binding agreements on carbon emissions (Dai, Xie, Xie, Liu, & Masui, 2016;He, 2010). Despite the efforts, however, the relation between economic prosperity and sustainable development presents issues for all nations, as the narrative of competing for wealth equating to success is fundamentally counter to cooperating to conserve the environment; at the individual level, this is further reinforced by education programs that often prioritise students' test performance over environmental education (Witoszek, 2018). A study by Sternäng and Lundholm (2011) explicitly focusing on environmental education highlights a confluence of these issues, where researchers had to convince the students being interviewed that they were not being assessed, as students seemed to be providing 'ethically correct' answers in line with their school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of being a significant contributor to climate change, China has taken a stance of leading through action rather than forcing other nations in binding agreements on carbon emissions (Dai, Xie, Xie, Liu, & Masui, 2016;He, 2010). Despite the efforts, however, the relation between economic prosperity and sustainable development presents issues for all nations, as the narrative of competing for wealth equating to success is fundamentally counter to cooperating to conserve the environment; at the individual level, this is further reinforced by education programs that often prioritise students' test performance over environmental education (Witoszek, 2018). A study by Sternäng and Lundholm (2011) explicitly focusing on environmental education highlights a confluence of these issues, where researchers had to convince the students being interviewed that they were not being assessed, as students seemed to be providing 'ethically correct' answers in line with their school.…”
Section: Discussionmentioning
confidence: 99%
“…However, research suggests that students must be made aware of specific behavioural changes to achieve the desired outcomes, as well as develop a problem-solving mentality to deal with the complex uncertainties that climate problems exhibit (Anderson, 2013;Birkmann & Welle, 2016;Pruneau et al, 2003). Of critical importance is 'educating the educators', to make them capable of dealing with the task; though not necessarily time-consuming, policy must address the issue in order to transfer the behavioural outcomes to their students (Anderson, 2013;Witoszek, 2018). Additionally, other outputs of the BN can provide important insights for policy-makers; for instance, because selfefficacy 'naturally' increases with the level of education, Australian and Chinese governments should focus their efforts on climate change education programs' implementation at early stages of the students' learning journey, such as in high school.…”
Section: Discussionmentioning
confidence: 99%
“…Given the sophisticated existing education system in China, ESD experts need to create a feasible ESD framework that takes this model into account. Even though EPD projects have supported ESD implementation in more than 1000 schools in China, this study and other field studies have indicated that these ESD practices may not be as robust as desired (Wang, 2011;Witoszek, 2018). Exam pressures have been widely discussed across China over last decades.…”
Section: Discussionmentioning
confidence: 76%
“…Aside from the absence of ESD policies, case studies in China's schools have also shown gaps in ESD curriculum and pedagogy implementation. Interview results from the "ESD demonstration school" of Jingshan in Beijing, China have shown that there is a lack of guidance from the education department about how to integrate ESD effectively (Witoszek, 2018). These interviews indicated the limited development of ESD on campus despite the fact that Jingshan school was one of the first labeled ESD schools in China (Witoszek, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation